Shot in America : television, the state, and the rise of Chicano cinema - Noriega, Chon A., 1961- (University of Minnesota Press, 2000)
Noriega offers a compelling and detailed description of an enormous body of work by Chicano media makers against the backdrop of Chicano social movements, politics, and activism over a forty-year period--an extraordinary exposition of the civil rights movement, media reform activities, and public affairs programming that constitutes the prehistory of independent and minority cinemas. 2000 Choice Outstanding Academic Title.